A Stiffness-Adjusting Method to Improve Thrust Efficiency of a Two-Joint Robotic Fish. (29th April 2014) - Xu, Dong; Zhang, Shaoguang; Wen, Li
Abstract : Fish are very efficient swimmers. In this paper, we studied a two degree-of-freedom (DOF) propeller that mimic fish caudal fin like locomotion. Kinematics modelling and hydrodynamic CFD analyses of the two DOF propellers were conducted. According to the CFD simulation, we show that negative power was generated within the flapping cycle, and wake flow at different instant was demonstrated. Based on the dynamic model, we compared the thrust efficiency under different stiffness control method. The results show that the thrust efficiency was enhanced under moderate stiffness control strategy.